The mediation effect of intention to use information system on the association between usability and user's satisfaction in UMP - Atta, Mohammed Thamir; Awanis, Romli (American Scientific Publishers, 2018)
Student Information Systems (SIS) have become an integral part of the function of most large and medium organizations including educational institutions. The aim of this research is to investigate the mediation role of intention to use SIS on the relationship between the usability of the system and user's satisfaction. A survey has been conducted in Universiti Malaysia Pahang to investigate the mediation relationships between these three variables. After collecting data from respondents and accomplishing the analysis, the result of this study revealed that the relationship between usability of SIS and user’s satisfaction is partially mediated by intention to use these systems. Based on this result, the researcher recommends focusing on the factors that enhance usability of SIS which in turn increase the intention of students to use the system and boost their satisfaction about the system. These factors are easy to use the interface, effective navigation, usefulness, and understandable website.